Digital Hubbub. - Wallich, P. (IEEE spectrum)
It records, it archives, it plays video and music. It organizes the family photos. It distributes digital signals around the home. "It" is the digital hub, and it could become the entertainment gateway to the home. More than a half-dozen companies so far are scrambling for the billions of dollars they hope to reap by offering consumers a single machine to handle their home entertainment needs. The companies agree on what the machine should do: record, archive, and play back video and music, organize digital photo albums, and distribute digital media around the home. Where they disagree is on what shape the machine should take. As might be expected, each company is casting this new species in its own image. To Apple and Microsoft, it looks like a computer. To cable and satellite companies like Charter, Echostar, or DirecTv and their suppliers, it's a set-top box. To consumer electronics companies like Philips or Samsung a stereo component. In shaping digital home entertainment, several crucial issues must be addressed. How will different pieces of software written by competing companies work together? Who will pay for the digital hubs and put them in homes? Who owns the material stored on a hub's hard disk, and who, legally, can control how it is transferred and displayed? These issues are discussed in this article